Characterization and analysis of plastic instability in an ultrafine‐grained medium Mn TRIP steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlon; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Additively Manufactured Nested and Non-Nested Cellular Solids for Effective Stress Distribution and Thermal Insulation Applications: An Experimental and Finite Element Analysis Study - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
In this study, the design, additive manufacturing and experimental as well as simulation investigation of mechanical and thermal properties of cellular solids are addressed. For this, two cellular solids having nested and non-nested structures are designed and additively manufactured via laser powder bed fusion. The primary objective is to design cellular solids which absorb a significant amount of energy upon impact loading without transmitting a high amount of stress into the cellular solids. Therefore, compression testing of the two cellular solids is performed. The nested and non-nested cellular solids show similar energy absorption properties; however, the nested cellular solid transmits a lower amount of stress in the cellular structure compared to the non-nested cellular solid. The experimentally measured strain (by DIC) in the interior region of the nested cellular solid is lower despite a higher value of externally imposed compressive strain. The second objective of this study is to determine the thermal insulation properties of cellular solids. For measuring the thermal insulation properties, the samples are placed on a hot plate; and the surface temperature distribution is measured by an infrared camera. The thermal insulating performance of both cellular types is sufficient for temperatures exceeding 100 °C. However, the thermal insulating performance of a non-nested cellular solid is slightly better than that of the nested cellular solid. Additional thermal simulations predict a relatively higher temperature distribution on the cellular solid surfaces compared to experimental results. The simulated residual stress shows a similar distribution for both types, but the magnitude of residual stress is different for the cellular solids upon cooling from different temperatures of the hot plate.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-functional PVD thin films deposited onto additively manufactured Ti6Al7Nb for biomedical applications - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Kokalj, David; Stangier, Dominic; Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko; Gödecke, Daria; Oltmanns, Hilke; Meißner, Jessica (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization and Analysis of Plastic Instability in an Ultrafine‐Grained Medium Mn TRIP Steel - Teng, Zhenjie; Wu, Haoran; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Zhang, Hanlong; Boller, Christian; Starke, Peter (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Modification of Iron with Degradable Silver Phases Processed via Laser Beam Melting for Implants with Adapted Degradation Rate - Krüger, Jan Tobias; Hoyer, Kay-Peter; Andreiev, Anatolii; Schaper, Mirko; Zinn, Carolin (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Additively manufactured novel Ti6Al7Nb circular honeycomb cellular solid for energy absorbing applications - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Additively Manufactured Nested and Non-Nested Cellular Solids for Effective Stress Distribution and Thermal Insulation Applications: An Experimental and Finite Element Analysis Study - Pramanik, Sudipta; Milaege, Dennis; Hoyer, Kay-Peter; Schaper, Mirko (Crystals)
In this study, the design, additive manufacturing and experimental as well as simulation investigation of mechanical and thermal properties of cellular solids are addressed. For this, two cellular solids having nested and non-nested structures are designed and additively manufactured via laser powder bed fusion. The primary objective is to design cellular solids which absorb a significant amount of energy upon impact loading without transmitting a high amount of stress into the cellular solids. Therefore, compression testing of the two cellular solids is performed. The nested and non-nested cellular solids show similar energy absorption properties; however, the nested cellular solid transmits a lower amount of stress in the cellular structure compared to the non-nested cellular solid. The experimentally measured strain (by DIC) in the interior region of the nested cellular solid is lower despite a higher value of externally imposed compressive strain. The second objective of this study is to determine the thermal insulation properties of cellular solids. For measuring the thermal insulation properties, the samples are placed on a hot plate; and the surface temperature distribution is measured by an infrared camera. The thermal insulating performance of both cellular types is sufficient for temperatures exceeding 100 °C. However, the thermal insulating performance of a non-nested cellular solid is slightly better than that of the nested cellular solid. Additional thermal simulations predict a relatively higher temperature distribution on the cellular solid surfaces compared to experimental results. The simulated residual stress shows a similar distribution for both types, but the magnitude of residual stress is different for the cellular solids upon cooling from different temperatures of the hot plate.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Coupled microscopic and micromagnetic depth-specific analysis of plastic deformation and phase transformation of metastable austenitic steel AISI 304L by flow forming - Rozo Vasquez, Julian; Kanagarajah, Hanigah; Arian, Bahman; Kersting, Lukas; Homberg, Werner; Trächtler, Ansgar; Walther, Frank (Practical Metallography)
Abstract This paper presents the characterization of the microstructure evolution during flow forming of austenitic stainless steel AISI 304L. Due to plastic deformation of metastable austenitic steel, phase transformation from γ-austenite into α’-martensite occurs. This is initiated by the formation of shear bands as product of the external stresses. By means of coupled microscopic and micromagnetic investigations, a characterization of the microstructure was carried out. In particular, this study shows the distribution of the strain-induced α’-martensite and its influence on material properties like hardness at different depths. The microstructural analyses by means of electron backscattered diffraction (EBSD) technique, evidence a higher amount of α’-martensite (ca. 23 %) close to the outer specimen surface, where the plastic deformation and the direct contact with the forming tool take place. In the middle area (ca. 1.5 mm depth from the outer surface), the portion of transformed α’-martensite drops to 7 % and in the inner surface to 2 %. These results are well correlated with microhardness and micromagnetic measurements at different depths. EBSD and atomic force microscopy (AFM) were used to make a detailed characterization of the topography and degree of deformation of the shear bands. Likewise, the mechanisms of nucleation of α’-martensite were discussed. This research contributes to the development of micromagnetic sensors to monitor the evolution of properties during flow forming. This makes them more suitable for closed-loop property control, which offers possibilities for an application-oriented and more efficient production.
Keywords: Metals and Alloys; Mechanics of Materials; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Low Temperature Laser Sintering with PA12 and PA6 on a Standard System - Menge, Dennis; Schmid, Hans-Joachim (Macromolecular Symposia)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry; Condensed Matter Physics

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; Kollmann, S.; Carlet, M.; de los Arcos de Pedro, Maria Teresa (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Insights into the decomposition of zirconium acetylacetonate using synchrotron radiation: Routes to the formation of volatile Zr-intermediates - Grimm, Sebastian; Baik, Seung-Jin; Hemberger, Patrick; Kasper, Tina; Kempf, Andreas M.; Atakan, Burak (Journal of Materials Research)
Abstract The thermal decomposition of Zr(acac) 4 is studied in a SiC-microreactor on the micro-second time scale. By utilizing synchrotron radiation and photoelectron photoion coincidence spectroscopy, six important zirconium intermediates, as for instance Zr(C 5 H 7 O 2 ) 2 (C 5 H 6 O 2 ), and Zr(C 5 H 6 O 2 ) 2 , are identified in the gas phase for the first time. The adiabatic ionization thresholds of intermediately formed zirconium species are estimated and the main products of their thermal decomposition, acetylacetone, acetylallene and acetone are characterized unambiguously and isomer-selectively. Based on all detected intermediates, we deduce the predominant pyrolysis pathways of the precursor in the temperature range from 400 to 900 K. Our findings are complemented by numerical simulations of the flow field in the microreactor, which show that the choice of dilution gas significantly influences the temperature profile and residence times in the microreactor, such that helium provides a more uniform flow field than argon and should preferentially be used. Graphical abstract Using a soft ionization method coupled to velocity map imaging (VMI), leads to valuable insights in the thermal decomposition of Zr(C 5 H 7 O 2 ) 4 , used in the synthesis of functional nanomaterials and ceramic coatings. Thanks to the use of a microreactor, important gas
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Model-based design of a segmented reactor for the flexible operation of the methanation of CO2 - Herrmann, Felix; Grünewald, Marcus; Riese, Julia (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Thermodynamic Properties of Methyl Diethanolamine - Neumann, Tobias; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran; Thol, Monika (International Journal of Thermophysics)
Abstract The homogeneous density of the liquid phase is experimentally investigated for methyl diethanolamine. Data are obtained along five isotherms in a temperature range between 300 K and 360 K for pressures up to 95 MPa. Two different apparatuses are used to measure the speed of sound for the temperatures between 322 K and 450 K with a maximum pressure of 95 MPa. These measurements and literature data are used to develop a fundamental equation of state for methyl diethanolamine. The model is formulated in terms of the Helmholtz energy and allows for the calculation of all thermodynamic properties in gaseous, liquid, supercritical, and saturation states. The experimental data are represented within their uncertainties. The physical and extrapolation behavior is validated qualitatively to ensure reasonable calculations outside of the range of validity. Based on the experimental datasets, the equation of state is valid for temperatures from 250 K to 750 K and pressures up to 100 MPa.
Keywords: Condensed Matter Physics

Durability of nanolayer Ti–Al–O–N hard coatings under simulated polycarbonate melt processing conditions - Brögelmann, T; Bobzin, K; Grundmeier, Guido; de los Arcos, T; Kruppe, N C; Schwiderek, S; Carlet, M (Journal of Physics D: Applied Physics)
Keywords: Surfaces; Coatings and Films; Acoustics and Ultrasonics; Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Atomic Layer Deposition of Copper Metal Films from Cu(acac) 2 and Hydroquinone Reductant - Tripathi, Tripurari Sharan; Wilken, Martin; Hoppe, Christian; de los Arcos, Teresa; Grundmeier, Guido; Devi, Anjana; Karppinen, Maarit (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

A 2–20-GHz Ultralow Phase Noise Signal Source Using a Microwave Oscillator Locked to a Mode-Locked Laser - Bahmanian, Meysam; Scheytt, J. Christoph (IEEE Transactions on Microwave Theory and Techniques)
Keywords: Electrical and Electronic Engineering; Condensed Matter Physics; Radiation

A 2–20-GHz Ultralow Phase Noise Signal Source Using a Microwave Oscillator Locked to a Mode-Locked Laser - Bahmanian, Meysam; Scheytt, J. Christoph (IEEE Transactions on Microwave Theory and Techniques)
Keywords: Electrical and Electronic Engineering; Condensed Matter Physics; Radiation

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas D (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

On topological materials as photocatalysts for water splitting by visible light - Ranjbar, Ahmad; Mirhosseini, Hossein; Kühne, Thomas (Journal of Physics: Materials)
Abstract We performed a virtual materials screening to identify promising topological materials for photocatalytic water splitting under visible light irradiation. Topological compounds were screened based on band gap, band edge energy, and thermodynamics stability criteria. In addition, topological types for our final candidates were computed based on electronic structures calculated usingthe hybrid density functional theory including exact Hartree–Fock exchange. Our final list contains materials which have band gaps between 1.0 and 2.7 eV in addition to band edge energies suitable for water oxidation and reduction. However, the topological types of these compounds calculated with the hybrid functional differ from those reported previously. To that end, we discuss the importance of computational methods for the calculation of atomic and electronic structures in materials screening processes.
Keywords: Condensed Matter Physics; General Materials Science; Atomic and Molecular Physics; and Optics

Anomalous bulk diffusion of methylene diphenyl diisocyanate in silicone elastomer - Wortmann, Martin; Viertel, Klaus; Welle, Alexander; Keil, Waldemar; Frese, Natalie; Hachmann, Wiebke; Krieger, Philipp; Brikmann, Johannes; Schmidt, Claudia; Moritzer, Elmar; Hüsgen, Bruno (International Journal of Heat and Mass Transfer)
Keywords: Fluid Flow and Transfer Processes; Mechanical Engineering; Condensed Matter Physics

Mechanism and equilibrium thermodynamics of H- and J-aggregate formation from pseudo isocyanine chloride in water - Hämisch, Benjamin; Huber, Klaus (Soft Matter)
Pseudo isocyanine chloride monomers equilibrate with H-oligomers and, separated by a threshold, with H-oligomers and fiber-like J-aggregates. The mechanism and thermodynamics of J-aggregate formation is interpreted with the concept of chain growth.
Keywords: Condensed Matter Physics; General Chemistry

Spin Polarization, Electron–Phonon Coupling, and Zero-Phonon Line of the NV Center in 3C-SiC - Jurgen von Bardeleben, Hans; Cantin, Jean-Louis; Gerstmann, Uwe; Schmidt, Wolf Gero; Biktagirov, Timur (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Strength enhancement of AlMg sheet metal parts by rapid heating and subsequent cold die stamping of severely cold-rolled blanks - Camberg, Alan Adam; Andreiev, Anatolii; Pramanik, Sudipta; Hoyer, Kay-Peter; Tröster, Thomas; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Additively processed TiAl6Nb7 alloy for biomedical applications - Hein, Maxwell; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-mechanical properties and biocompatibility of Ag-containing amorphous carbon films deposited onto Ti6Al4V - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Franke, Carlo; Kokalj, David; Stangier, Dominic; Filor, Viviane; Mateus-Vargas, Rafael Hernán; Oltmanns, Hilke; Kietzmann, Manfred; Meißner, Jessica; Hein, Maxwell; Pramanik, Sudipta; et al. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Laser beam melting of functionally graded materials with application-adapted tailoring of magnetic and mechanical performance - Andreiev, Anatolii; Hoyer, Kay-Peter; Dula, Dimitri; Hengsbach, Florian; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Bioresorbable AgCe and AgCeLa alloys for adapted Fe-based implants - Krüger, Jan Tobias; Hoyer, Kay-Peter; Schaper, Mirko (Materials Letters)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Anisotropic Ion Migration and Electronic Conduction in van der Waals Ferroelectric CuInP2S6 - Zhang, Dawei; Luo, Zheng-Dong; Yao, Yin; Schoenherr, Peggy; Sha, Chuhan; Pan, Ying; Sharma, Pankaj; Alexe, Marin; Seidel, Jan (Nano Letters)
Keywords: Mechanical Engineering; Condensed Matter Physics; General Materials Science; General Chemistry; Bioengineering

Bright Electrically Controllable Quantum‐Dot‐Molecule Devices Fabricated by In Situ Electron‐Beam Lithography - Schall, Johannes; Deconinck, Marielle; Bart, Nikolai; Florian, Matthias; Helversen, Martin; Dangel, Christian; Schmidt, Ronny; Bremer, Lucas; Bopp, Frederik; Hüllen, Isabell; Gies, Christopher; Reuter, Dirk; et al. (Advanced Quantum Technologies)
Keywords: Electrical and Electronic Engineering; Computational Theory and Mathematics; Condensed Matter Physics; Mathematical Physics; Nuclear and High Energy Physics; Electronic; Optical and Magnetic Materials; Statistical and Nonlinear Physics

“Seeing Is Believing”—In-Depth Analysis by Co-Imaging of Periodically-Poled X-Cut Lithium Niobate Thin Films - Reitzig, Sven; Rüsing, Michael; Zhao, Jie; Kirbus, Benjamin; Mookherjea, Shayan; Eng, Lukas M. (Crystals)
Nonlinear and quantum optical devices based on periodically-poled thin film lithium niobate (PP-TFLN) have gained considerable interest lately, due to their significantly improved performance as compared to their bulk counterparts. Nevertheless, performance parameters such as conversion efficiency, minimum pump power, and spectral bandwidth strongly depend on the quality of the domain structure in these PP-TFLN samples, e.g., their homogeneity and duty cycle, as well as on the overlap and penetration depth of domains with the waveguide mode. Hence, in order to propose improved fabrication protocols, a profound quality control of domain structures is needed that allows quantifying and thoroughly analyzing these parameters. In this paper, we propose to combine a set of nanometer-to-micrometer-scale imaging techniques, i.e., piezoresponse force microscopy (PFM), second-harmonic generation (SHG), and Raman spectroscopy (RS), to access the relevant and crucial sample properties through cross-correlating these methods. Based on our findings, we designate SHG to be the best-suited standard imaging technique for this purpose, in particular when investigating the domain poling process in x-cut TFLNs. While PFM is excellently recommended for near-surface high-resolution imaging, RS provides thorough insights into stress and/or defect distributions, as associated with these domain structures. In this context, our work here indicates unexpectedly large signs for internal fields occurring in x-cut PP-TFLNs that are substantially larger as compared to previous observations in bulk LN.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Photoconduction of Polar and Nonpolar Cuts of Undoped Sr0.61Ba0.39Nb2O6 Single Crystals - Beyreuther, Elke; Ratzenberger, Julius; Roeper, Matthias; Kirbus, Benjamin; Rüsing, Michael; Ivleva, Liudmila I.; Eng, Lukas M. (Crystals)
In the last two decades, variably doped strontium barium niobate (SBN) has attracted a lot of scientific interest mainly due to its specific non-linear optical response. Comparably, the parental compound, i.e., undoped SBN, appears to be less studied so far. Here, two different cuts of single-crystalline nominally pure strontium barium niobate in the composition Sr0.61Ba0.39Nb2O6 (SBN61) are comprehensively studied and analyzed with regard to their photoconductive responses. We present conductance measurements under systematically varied illumination conditions along either the polar z-axis or perpendicular to it (x-cut). Apart from a pronounced photoconductance (PC) already under daylight and a large effect upon super-bandgap illumination in general, we observe (i) distinct spectral features when sweeping the excitation wavelength over the sub-bandgap region as then discussed in the context of deep and shallow trap states, (ii) extremely slow long-term relaxation for both light-on and light-off transients in the range of hours and days, (iii) a critical dependence of the photoresponse on the pre-illumination history of the sample, and (iv) a current–voltage hysteresis depending on both the illumination and the electrical-measurement conditions in a complex manner.
Keywords: Inorganic Chemistry; Condensed Matter Physics; General Materials Science; General Chemical Engineering

Kinetic studies of cathode degradation on PEM fuel cell short stack level undergoing freeze startups with different states of residual water and current draws - Liphardt, L.; Suematsu, K.; Grundmeier, Guido (International Journal of Hydrogen Energy)
Keywords: Energy Engineering and Power Technology; Condensed Matter Physics; Fuel Technology; Renewable Energy; Sustainability and the Environment

Effects of KF and RbF treatments on Cu(In,Ga)Se2-based solar cells: A combined photoelectron spectroscopy and DFT study - Majumdar, I.; Sahoo, S.K.; Parvan, V.; Mirhosseini, Hossein; Chacko, B.; Wang, Y.; Greiner, D.; Kühne, Thomas; Schlatmann, R.; Lauermann, I. (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

InAs heteroepitaxy on nanopillar-patterned GaAs (111)A - Kunnathully, Vinay S.; Riedl, Thomas; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Journal of Crystal Growth)
Keywords: Materials Chemistry; Inorganic Chemistry; Condensed Matter Physics

Applicability of molecular statics simulation to partial dislocations in GaAs - Riedl, Thomas; Lindner, Jörg (Solid State Communications)
Keywords: Materials Chemistry; Condensed Matter Physics; General Chemistry

Applicability of molecular statics simulation to partial dislocations in GaAs - Riedl, Thomas; Lindner, Jörg (Solid State Communications)
Keywords: Materials Chemistry; Condensed Matter Physics; General Chemistry

Dynamics of a liquid crystal-based modulator with germanium substrates for mid-infrared radiation - Risse, Anna Margareta; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Water structure near the surface of Weyl semimetals as catalysts in photocatalytic proton reduction - Gujt, Jure; Zimmer, Peter; Zysk, Frederik; Süß, Vicky; Felser, Claudia; Bauer, Matthias; Kühne, Thomas (Structural Dynamics)
Keywords: Spectroscopy; Condensed Matter Physics; Instrumentation; Radiation

Roadmap on quantum light spectroscopy - Mukamel, Shaul; Freyberger, Matthias; Schleich, Wolfgang; Bellini, Marco; Zavatta, Alessandro; Leuchs, Gerd; Silberhorn, Christine; Boyd, Robert W; Sánchez-Soto, Luis Lorenzo; Stefanov, André; Barbieri, Marco; Paterova, Anna; et al. (Journal of Physics B: Atomic, Molecular and Optical Physics)
Keywords: Condensed Matter Physics; Atomic and Molecular Physics; and Optics

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christoph; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Condensed Matter Physics

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Degradable silver‐based alloys - Andreiev, Anatolii; Hoyer, Kay-Peter; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Preparation of Light-Responsive Aliphatic Polycarbonate via Versatile Polycondensation for Controlled Degradation - Sun, Jingjiang; Anderski, Juliane; Picker, Marie-Theres; Langer, Klaus; Kuckling, Dirk (Macromolecular Chemistry and Physics)
Keywords: Materials Chemistry; Organic Chemistry; Polymers and Plastics; Physical and Theoretical Chemistry; Condensed Matter Physics

The Stokes Limit in a Three-Dimensional Chemotaxis-Navier–Stokes System - Black, Tobias (Journal of Mathematical Fluid Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Condensed Matter Physics; Mathematical Physics